Improvement of the Concept of the Image of the Enterprise for the Account of Social-Ecological Public Effects - Dergousova, Alla; Elagin, Yuriy; Chebanova, Oksana (International Journal of Engineering and Technology, 2018)
The concept of enterprise image and social responsibility has been studied. It has been proved that in the global civilized business environment, it is necessary to rely on moral and social aspects to achieve competitive advantages and consumer loyalty. It has been identified that the formation of a sustainable image of an enterprise is the readiness of the company to be responsible to society, namely, to care for the environment, the health of consumers, and for observing their consumer and civil rights. It has been found out that the creation of the company's image is also influenced by environmental responsibility of the enterprise. The experience in implementation of social and environmental responsibility at the enterprises of the European Union has been analyzed. The concept of the company's image is improved due to the scientific justification for the need to introduce social and environmental components as weighty factors affecting the corporate strategy. This will make it possible to increase the competitiveness and image of the enterprise, to form a high level of loyalty to the enterprise's products in a consumerâ€™s mind.Â Â